THE RELATIONSHIP BETWEEN THE AVAILABILITY OF LACTATION FACILITIES, MOTHERS' KNOWLEDGE, AND EXCLUSIVE BREASTFEEDING AMONG FEMALE FACTORY WORKERS IN SIDOARJO DISTRICT - Billah Rizqa; Chatarina Umbul W (Universitas Airlangga, 2021)
ABSTRACTAccording to UNICEF, in 2013 there were 136,700,000 live births, but only about 32.6% of these babies received breast milk exclusively. In developing countries, only about 39% of mothers breastfeed exclusively. Indonesia has targetted for 80% exclusive breastfeeding. However, it has not been achieved. A large number of women in the workforce and the unavailability of breastfeeding facilities are among the factors influencing the low coverage of exclusive breastfeeding in Indonesia. In addition, maternal knowledge is also a contributing factor for exclusive breastfeeding practices This study aims to analyze the relationship between the availability of lactation facilities and maternal knowledge with exclusive breastfeeding. The execution of this research was conducted quantitatively with the descriptive research type. The design of this study is case-control. The study’s population were female factory workers who had babies in Sidoarjo District. The sample size is 42 case samples and 42 control samples. The research sample was taken using a simple random sampling technique. The data was retrieved through survey methods with questionnaires. The results of the study show that there is no relationship between knowledge and exclusive breastfeeding (p = 0.200) and there is a relationship between the availability of lactation facilities and exclusive breastfeeding (p = 0.049). Mothers who work in factories with lactation facilities have a 2.667 times greater opportunity to give exclusive breastfeeding to their babies than mothers without access to lactation facilities (OR = 2.667). The researchers suggest factories to provide lactation facilities and visitation activities by the local health office.Keywords: Exclusive breastfeeding, Lactation facilities, Mother's knowledge